EKSTRAK BUAH MANGROVE (Sonneratia alba) PADA Artemia salina DALAM MENGHAMBAT INFEKSI Vibrio harveyi TERHADAP SINTASAN BENUR UDANG WINDU (Penaeus monodon) SECARA INVIVO - cahyadi, jimmy; Satriani, Gloria Ika; Gusman, Ery; Sabri, Sabri (Fakultas Perikanan Dan Ilmu Kelautan Universitas Borneo Tarakan, 2019)
Â Vibriosis disease Vibrio harveyi often drops Penaeus monodon production on the traditional coastal ponds of North Kalimantan. The purpose of this study was to find out the active compound extract of Sonneratia alba fruit inhibiting the infection of Vibrio harveyi, which was tested on the larvae of Penaeus monodon in post larvae 12 through the bioerichment of natural feed Artemia salina. This study used an experimental method performed with a Completely Randomized Design (CRD) of 4 treatments and 3 replications. The results showed mangrove fruit extracts containing alkaloids, phenol hydroquinone, flavonoids, saponins, steroids and tannins. Artemia salina bioenrichment succeeded in increasing the survival of Penaeus monodon larvae 78.33% in treatment III (20 ppm). The results of water quality measurements indicate the range at the normal limit for the life of the Penaeus monodon larvae.Â Keywords : Penaeus monodon, Artemia salina, Vibrio harveyi, Extract Sonneratia alba